If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2z + -19 = z + -10 Reorder the terms: -19 + -2z = z + -10 Reorder the terms: -19 + -2z = -10 + z Solving -19 + -2z = -10 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. -19 + -2z + -1z = -10 + z + -1z Combine like terms: -2z + -1z = -3z -19 + -3z = -10 + z + -1z Combine like terms: z + -1z = 0 -19 + -3z = -10 + 0 -19 + -3z = -10 Add '19' to each side of the equation. -19 + 19 + -3z = -10 + 19 Combine like terms: -19 + 19 = 0 0 + -3z = -10 + 19 -3z = -10 + 19 Combine like terms: -10 + 19 = 9 -3z = 9 Divide each side by '-3'. z = -3 Simplifying z = -3
| 6p-12=15 | | 88=-8(r-4) | | -3a-7=5a-23 | | 5+20=-5(6x-5) | | 0.05(x-7000)+0.02x=1120 | | 3day=second | | 5(b+6)-4(b+2)=24 | | x=60+0.50*130 | | 7x-7w-4x+6y+3y+4w= | | (x+30)y=14 | | x^2+3x=3x+36 | | 5(x+10)=20x+5 | | 0.05(x-7000)+0.06x=1120 | | 5(x-1)-5=13 | | 5(t-12)=6 | | -6p+7=-6 | | 4n-16=6n | | 5x+15-20=10x-15 | | x=60+0.50*1.30 | | ln(6x+9)=ln(4x-11) | | 5(b+1)+10=6 | | 4-8d=6-8d | | 4x-(-4)=-4 | | 0.05(x-5000)+0.06x=1620 | | 6z-11=4-3 | | X=2y-z(z) | | x=60+.50n | | 13x+3-2x=11x-5+8 | | 2x^8=624 | | 0.2(3x+4)= | | 56-0.25f=f-3 | | 2(x-45)=3x |